Mass spectrometry for characterization of homologous piperidine alkaloids and their activity as acetylcholinesterase inhibitors - Freitas, Thamires R.; Danuello, Amanda; Viegas Junior, Claudio; Bolzani, Vanderlan S. [UNESP]; Pivatto, Marcos (Wiley-Blackwell, 2018)
RationalePiperidine alkaloids from Senna spectabilis constitute a rare class of natural products with several biological activities. However, the absence of chromophores makes their structural elucidation by conventional methods a great challenge. In this context, mass spectrometry emerges as a powerful tool for metabolomics studies. MethodsThe piperidine alkaloids (-)-cassine and (-)-spectaline and the semisynthetic derivatives (-)-3-O-acetylcassine and (-)-3-O-acetylspectaline were investigated by electrospray ionization tandem mass spectrometry (ESI-MS/MS) in the positive mode and electron ionization mass spectrometry (EI-MS). ESI fragmentation studies were performed with a quadrupole time-of-flight instrument; N-2 was used as collision gas. The acetylcholinesterase inhibitory activity of the investigated compounds was evaluated by bioautography and microplate screening assays. ResultsESI-MS/MS and EI-MS provided valuable and complementary information about the structure of the piperidine compounds. Collision-induced dissociation experiments (MS/MS) revealed that neutral elimination of water or acetic acid is the major fragmentation pathway, which agrees with the stereochemistry proposed for (-)-cassine and (-)-spectaline and the semisynthetic derivatives (-)-3-O-acetylcassine and (-)-3-O-acetylspectaline. ConclusionsThe ESI-MS/MS and EI-MS studies allowed us to propose fragmentation mechanisms for piperidine alkaloids and derivatives. Therefore, mass spectrometry is an important tool for characterizing the structure of these compounds and for supporting further metabolomics studies.